Tax Dimension of Internet Advertising in Turkey - Şeyma Demirel; Hakan Arslaner (Maliye Çalışmaları Dergisi)
Earnings from digital platforms have increased exponentially, given the impact of the digital age and technological development. Therefore, the demand and attraction of this form of revenue generation has also increased. In terms of the digital economy, location of the provision of the service and the location of income beneficiary may differ. As a result of lack of regulation regarding the activities performed in the digital environment based on geographical boundaries, the challenge of sales taxation for the income obtained in this field has emerged. In this context, certain regulations have been established in the international arena to determine the revenue obtained from internet advertising services offered and the country of taxation authority. The Organisation for Economic Co-operation and Development assert that international tax regulations should be rearranged to include digital environments and has recently launched studies on this issue. The European Union Commission has also raised the issue of Digital Service Tax for the taxation of digital activities. In this study, the taxation of internet advertising is discussed within the framework of international tax regulations and tax laws in Turkey. Accordingly, it was concluded that some important and fair regulations have been applied in terms of taxing internet advertising.